How clinicians experience a simulated antiretroviral therapy adherence exercise: A qualitative study - Justin G. Engelbrecht; Fidele K. Mukinda; Beryl Green; Donald Skinner (AOSIS, 2018)
Background: With the shift of paediatric antiretroviral therapy (ART) from tertiary to primary health care, there has been a need to train clinicians working in primary health care facilities to support adherence to treatment. An adherence simulation exercise was included in a course on paediatric human immunodeficiency virus (HIV) and tuberculosis (TB) to stimulate health care providers' awareness and generate empathy of complex paediatric adherence practices. Aim: The aim of this study was to describe the experience of clinicians completing the simulation exercise and to assess whether enhancing their empathy with patients and treatment supporters would improve their perceived clinical and counselling skills. Setting: The study was conducted at the Faculty of Medicine and Health Sciences, Stellenbosch University, and a guesthouse in Cape Town. Methods: The adherence module used blended learning methodology consisting of face-to-face contact sessions and distance learning. A qualitative thematic approach was used to understand the participant experiences through focus-group discussions and semi-structured interviews. Results: Three thematic clusters emerged, namely, experiences of the simulated exercise, patient-provider relationships and adherence strategies. Their experiences were both positive and challenging, especially when a 'caregiver and/or treatment supporter' scenario encouraged participants to reflect on their own relationships with their patients. Clinicians had also considered how empathy fits into their scope of responsibilities. Text messaging and adherence counselling strategies were identified. Conclusion: Simulated learning activities have the potential to create awareness of relationships between clinicians and their patients and generate ideas and discussion that could lead to improvements in clinical practice, and adherence promotion strategies.